Do children report differently from their parents and from observed data? Cross-sectional data on fruit, water, sugar-sweetened beverages and break-time foods. (December 2016) - van de Gaar, V.; Jansen, W.; van der Kleij, M.; Raat, H.
Abstract Background Reliable assessment of children's dietary behaviour is needed for research purposes. The aim of this study was (1) to investigate the level of agreement between observed and child-reported break-time food items; and (2) to investigate the level of agreement between children's reports and those of their parents regarding children's overall consumption of fruit, water and sugar-sweetened beverages (SSB). Methods The children in this study were 9–13 years old, attending primary schools in Rotterdam, the Netherlands. Children were observed with respect to foods brought for break-time at school. At the same day, children completed a questionnaire in which they were asked to recall the food(s) they brought to school to consume during break-time. Only paired data (observed and child-reported) were included in the analyses (n = 407 pairs). To determine each child's daily consumption and average amounts of fruit, water and SSB consumed, children and their parents completed parallel questionnaires. Only paired data (parent-reported and child-reported) were included in the analyses (n = 275 pairs). The main statistical measures were level of agreement between break-time foods, fruit, water and SSB; and Intra-class Correlation Coefficients (ICC). Results More children reported bringing sandwiches and snacks for break-time than was observed (73 % vs 51 % observed and 84 % vs 33 % observed). The overall agreement between observed and child-reported break-time foods was poor to fair, with ICC range 0.16–0.39 (p < 0.05). Children reported higher average amounts of SSB consumed than did their parents (1.3 vs 0.9 L SSB, p < 0.001). Child and parent estimations of the child's water and fruit consumption were similar. ICC between parent and child reports was poor to good (range 0.22–0.62, p < 0.05). Conclusion Children report higher on amount of break-time foods as compared to observations and children's reports of SSB consumption are higher than those of their parents. Since the level of agreement between the observed break-time foods and that reported by children and the agreement of child's intake between parent and child reports are relatively weak, future studies should focus on improving methods of evaluating children's consumption behaviour or on ways on how to best use and interpret multiple-source dietary intake data. Trial registration Current Controlled TrialsNTR3400 .